Perioperative hypothermia prevention: development of simple principles and practice recommendations using a multidisciplinary consensus-based approach - Fiona M Wood; Nicholas Ralph; Jed Duff; Judy Munday; David Sturgess; Mary-Anne Ramis (BMJ Open)
Objectives To develop a consensus on evidence-based principles and recommendations for perioperative hypothermia prevention in the Australian context.Design This study was informed by CAN-IMPLEMENT using the ADAPTE process: (1) formation of a multidisciplinary development team; (2) systematic search process identifying existing guidance for perioperative hypothermia prevention; (3) appraisal using the AGREE II Rigor of Development domain; (4) extraction of recommendations from guidelines meeting a quality threshold using the AGREE-REX tool; (5) review of draft principles and recommendations by multidisciplinary clinicians nationally and (6) subsequent round of discussion, drafting, reflection and revision by the original panel member team.Setting Australian perioperative departments.Participants Registered nurses, anaesthetists, surgeons and anaesthetic allied health practitioners.Results A total of 23 papers (12 guidelines, 6 evidence summaries, 3 standards, 1 best practice sheet and 1 evidence-based bundle) formed the evidence base. After evidence synthesis and development of draft recommendations, 219 perioperative clinicians provided feedback. Following refinement, three simple principles for perioperative hypothermia prevention were developed with supporting practice recommendations: (1) actively monitor core temperature for all patients at all times; (2) warm actively to keep body temperature above 36°C and patients comfortable and (3) minimise exposure to cold at all stages of perioperative care.Conclusion This consensus process has generated principles and practice recommendations for hypothermia prevention that are ready for implementation with local adaptation. Further evaluation will be undertaken in a large-scale implementation trial across Australian hospitals.